Association of KIR haplotypes with propensity for developing chronic hepatitis B induced liver diseases (cirrhosis and hepatocellular carcinoma) and HIV-1 infection in a West African Cohort - Florencia Wendkuuni Djigma; Pegdwendé Abel Sorgho; Marius Ayaovi Setor; Bolni Marius Nagalo; Bayala Bagora; Lassina Traore; Christelle WM Nadembega; Djeneba Ouermi; Albert Théophane Yonli; Simpore Jacques (Annals of Molecular and Genetic Medicine - Peertechz Publications, 2020)
Objectives: A subset of specialized KIR haplotype has been shown to be strongly associated with susceptibility or resistance to viral infections in humans. Therefore, this pilot investigation sought to determine the frequencies of KIR Haplotype in hepatitis B (HBV) and HIV-1 infected patients and their clinical impacts in disease progression and staging in Burkina Faso. Methods: Hepatitis B infected patients, Human Immunodeficiency virus type 1 (HIV-1) infected individuals and healthy individuals were selected for this study. Hepatitis B surface antigen (HBsAg), anti-HCV antibodies and anti-HIV-1/2 antibody/antigen were screened using a 4th generation ELISA assay (ARCHITECT I 1000SR®TM, Abbott Laboratories, USA). In addition, SSP-PCR was used to search the frequencies of KIR haplotype. HBV viral load and HIV-1 viral load was determined in patients along with the CD4+ count. Results: A and B KIR haplotypes was found to be associated with protection against HBV chronic infection evolution to cirrhosis (OR= 0.17, CI95% = 0.03-0.80, P= 0.03) and Hepato-Cellular Carcinoma (HCC) (OR= 0.32, CI95% = 0.11-0.92, P= 0.04). No association was found between markers of HIV infection and KIR haplotypes. No difference was found with regard to the Viral Load of HBV, HIV-1 and KIR haplotype. Conclusion: Our results suggest that A and B KIR haplotypes was associated with protection against HBV chronic infection evolution to cirrhosis and/or HCC. KIR haplotypes do not seem to be associated with immunosuppression status among HIV positive person. Further investigations are in need to fully understand the clinical significance of KIR Haplotype in HBV, HIV disease progression to improve patient's managements in Burkina.